English for everyone English idioms - Booth, Thomas (New York, New York DK Publishing, 2019)
"[This book] presents more than 1,000 idioms and expressions in context, with clear, simple definitions and attractive illustrations. Work through the tightly focused practice exercises and listen to the free audio to commit the English phrases to memory and make your English more fluent and natural."--
Describing people and things -- Attitude -- Situations and circumstances -- Communication -- Everyday life -- Work and achievements -- Expressions
Includes index
Internet connection needed for accompanying audio materials found on publisher's website at www.dkefe.com
Statement of responsibility from page opposite title page
Keywords: English language -- Textbooks for foreign speakers; English language -- Idioms -- Problems, exercises, etc; English language -- Terms and phrases -- Problems, exercises, etc; English language -- Idioms; English language -- Terms and phrases; English language; FOREIGN LANGUAGE STUDY / English as a Second Language; Problems and exercises; Problems and exercises; Textbooks -- for foreign speakers; Textbooks